2007
DOI: 10.1021/ja070259i
|View full text |Cite
|
Sign up to set email alerts
|

Concise, Asymmetric, Stereocontrolled Total Synthesis of Stephacidins A, B and Notoamide B

Abstract: Concise asymmetric total syntheses of the fungal metabolites (−)-stephacidin A, (+)-stephacidin B, and (+)-notoamide B are described. Key features of these total syntheses include (1) a facile synthesis of (R)-allyl proline methyl ester, (2) a revised route toward the pyranoindole ring system, (3) a novel cross-metathesis strategy for the introduction of important functional groups, and (4) an S N 2′ cyclization to form the [2.2.2] bridged bicyclic ring system. Furthermore, our synthesis has taken advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(69 citation statements)
references
References 43 publications
1
67
0
1
Order By: Relevance
“…Interestingly, Williams et al reported that treatment of the lactone 6 (R = allyl) with Na in methanol, followed by the addition of acetyl chloride to the solution and heating to reflux, readily removes the trichloroacetaldehyde auxiliary. [27] In this manner, (R)-allylproline methyl ester hydrochloride salt was prepared on a 20 g scale and was used as a building block for the total synthesis of the fungal metabolites (-)-stephacidin A, (+)-stephacidin B, and (+)-notoamide B. Besides this, the (trichloromethyl)oxazolidinones could also be readily transformed into amides by nucleophilic ring-opening with amines.…”
Section: Self-reproduction Of Chiralitymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Williams et al reported that treatment of the lactone 6 (R = allyl) with Na in methanol, followed by the addition of acetyl chloride to the solution and heating to reflux, readily removes the trichloroacetaldehyde auxiliary. [27] In this manner, (R)-allylproline methyl ester hydrochloride salt was prepared on a 20 g scale and was used as a building block for the total synthesis of the fungal metabolites (-)-stephacidin A, (+)-stephacidin B, and (+)-notoamide B. Besides this, the (trichloromethyl)oxazolidinones could also be readily transformed into amides by nucleophilic ring-opening with amines.…”
Section: Self-reproduction Of Chiralitymentioning
confidence: 99%
“…In particular, enantiomerically pure α-allylproline has shown plentiful applications in the synthesis of type II [29] and type VI [30] β-turn [31] mimetics, spirolactams [25,32] as conformationally restricted pseudopeptides, biologically active natural products, [21,27,33] and peptidomimetics. [24,34] As well as alkylation reactions, additions to carbonyl groups of aldehydes [17,35] and ketones, [17] Michael additions, [17] and acylation reactions [17,32b] have also been reported (Scheme 3).…”
Section: Self-reproduction Of Chiralitymentioning
confidence: 99%
“…via cations or radicals or anions. For example, S N 2' cyclizations of diketopiperazine (DKP) enolates were used by Williams' group in their approaches to both brevianamide B (I) [16,17] and stephacidin A (IV) [18][19][20][21][22], whereas Sarpong et al used an intramolecular enolate amidation [23]. Myers' [24] and Trost's [25,26] groups used radical cyclizations to construct the diazabicyclo[2.2.2]octane skeleton, whereas Simpkins' group developed both cationic [27][28][29] and radical [30,31] cyclization cascades to malbrancheamide B (V) and stephacidin A (IV), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of compound 57 with a palladium catalyst resulted in the formation of coupling product 59 through intermediate 58. 11 An early contribution for the synthesis of a pyrrole-containing natural product by using an intramolecular C-H arylation strategy. rhazinilam was achieved.…”
Section: Rhazinilam (Intramolecular and Intermolecular C-h Arylation mentioning
confidence: 99%